هجرة السوافة لإقليمي وادي ريغ والزيبان وإسهاهاتهم الدينية و الثقافية خلال القرن ال 20 م - عروة,حورية; وصيف سنوسي,نصيرة; عثماني,نورالهدى (University of Eloued جامعة الوادي, 2024)
تعالج هذه الدراسة هجرات السوافة الداخلية لإقليمي وادي ريغ والزيبان وإسهاماتهم الدينية والثقافية خلال القرن العشرين فجوهرها قائم على تسليط الضوء على المـجهودات الدينية والثقافية التي قدمها أبناء سوف في المنطقتين والتي أصبحت تراثا قيما وكنزا ثمينا بقيت معالمها شاهدة إلى اليوم. وقد تجسدت في الدور الذي لعبه أعلام سوف في تنشيطهم للحركة التعليمية القرآنية بالكتاتيب والمساهمة في التنوير الديني والوعظ الأخلاقي في المساجد والزوايا إلى جانب مساهمتهم في حركة الإصلاح الديني وبناء المساجد والزوايا التي أصبحت منطلقا لنشر تعاليم الدين الإسلامي. أما في الجانب الثقافي فيظهر دورهم جليا في حركة التأليف والأدب، حيث أنتجوا العديد من المؤلفات التي تركت بصمة واضحة في المكتبات الجزائرية، إضافة إلى تأسيس المدارس وتمويلها مما أسهم في رفع المستوى التعليمي ،كذلك إنشاء الصحف والكتابة فيها والتي ساهمت في تنوير المجتمع وتوعيته. This study deals with the internal migrations of the Souafa to the regions of Wadi Righ and Ziban and their religious andcultural contributions during the twentieth century. Its essence is based on shedding light on the religious and cultural efforts made by the sons of Souf in the two regions, which have become a valuable heritage and a precious treasure whose features remain a witness to this day. It was embodied in the role played by the notables of Souf in activating the Quranic educational movement in the Kuttabs and contributing to religious enlightenment and moral preaching in mosques and corners, in addition to their contribution to the religious reform movement and the construction of mosques and corners that became a starting point for spreading the teachings of the Islamic religion. As for the cultural aspect, their role is clearly evident in the movement of authorship and literature, as they produced many books that left a clear imprint on Algerian libraries, in addition to establishing and financing schools, which contributed to raising the educational level, as well as establishing newspapers and writing in them, which contributed to enlightening and educating society.
Keywords: migrations; religious contributions; cultural contributions; وادي ريغ; الإسهامات الدينية; الاسهامات الثقافية